THE EFFICIENCY ASSESSMENT OF THE EXTRA PREVENTION AGAINST FLU AND OTHER RESPIRATORY ACUTE VIRAL INFECTIONS AMONG CHILDREN AIDED BY ALFA 2B INTERFERON MEDICATION - M.G. Pozdnyakova; V.L. Maksakova; I.L. Kolyvanova; V.M. Nikolaeva; T.I. Krainova; S.V. Usova; M.K. Erofeeva (Union of pediatricians of Russia, 2006)
Among many medications recommended for the treatment and prevention against flu and other respiratory acute viral infections, inteferons and interferon inducers hold a special place. New Russian recombinant alpha 2b interferon is identical to the human leukocytic alpha 2b interferon, and it has an antiviral, immunomodulatory and interferonogenic action. The work has demonstrated the application of oral liposomal medication of recombinant alpha 2b interferon - reaferones lipint for the extra prevention against flu and other respiratory acute viral infections among children. the application of this medication to prevent flu and other respiratory acute viral infections in dosage of 250 000 ме twice a week for the period of 4 weeks proved to be efficient within the group of primary school aged children (aged 7-10 year old) and manifested itself in reduction of flu and respiratory acute viral infection cases, as well as domination of light for of disease run.Key words: flu, prevention, efficiency rate, interferon.